Analytical-Based application software for Estimating remaining fatigue life of Non-Cantilevered sign structures. (1st July 2022) - Alshareef, Husam A.; Al Shboul, Khalid W.; Rasheed, Hayder A.; Abouelleil, Alaaeldin
Highlights: Software for fatigue inspection of highway sign structures was developed. Wind database was built and developed to simulate an actual 45-year wind loading effects. A fluctuation model is established to generate cyclic wind behavior for fatigue calculation. The approach was confirmed to yield very accurate results compared to an actual case study. Abstract: This paper presents the development of an application framework software for accurately predicting the consumed fatigue life of overhead sign highway structures. The software was designed as a package tool to utilize a 45-year wind model and the finite element software Staad Pro platform in generating a multitude of simulations while adapting their results into a fatigue calculation engine. The applicability and validity of the developed environment in evaluating the fatigue life of structures was tested by blindly running the simulations for different structures. Given that, the remaining time span of a secondary column brace was predicted to be exhausted for a structure in Wichita, KS and the follow-up physical inspection confirmed that. Thus, it is believed that this present tool could be confidently used in predicting the initiation of fatigue cracks to alert the governmental agencies to take a proactive role in preventing the further collapse of these types of structures.